Small Cash Rewards for Big Losers : Experimental Insights into the Fight against the Obesity Epidemic - Augurzky, Boris (World Bank, Washington, DC, 2015)
This paper examines the sustainability of weight loss achieved through cash rewards and, for the first time, the potential of monetary incentives to prevent weight cycling. In a three period randomized controlled trial, about 700 obese persons were assigned to two treatment groups, which were promised different cash rewards contingent on the achievement of an individually assigned target weight, and to a control group. Successful participants were subsequently allocated to two treatment groups offered different monetary incentives for maintaining the previously achieved target weight and to a control group. This is the first experiment of this kind that finds sustainable effects of weight loss rewards on the body weight of the obese even 18 months after the rewards were removed. Additional incentives to maintain an achieved body weight improve the sustainability of weight loss only while are in place.